The effect of Bt-transgenic potatoes on the movement of the Colorado potato beetle [Coleoptera : Chrysomelidae] - Pelletier, Y.; Clark, C.; Boiteau, G.; Feldman-Riebe, J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2000)
A two-year field study conducted at the Potato Research Centre in Fredericton, New Brunswick, demonstrated a quantifiable residency time for Bacillus thuringiensis (Bt) susceptible adult Colorado potato beetles (Leptinotarsa decemlineata) in a Bt-transgenic potato field. Fifty percent of Bt-susceptible beetles released in a transgenic Russet Burbank (NewLeafTM) potato plot were recaptured 4 to 7 days after release compared to 7 to 11 days for beetles released in a non-transgenic control plot. Beetles survived for long periods of time (up to 31 days) on transgenic potatoes in spite of the crop's toxicity. A significant number of beetles dispersed from transgenic plots. Twenty-five and 30% of the beetles released in the Bt-transgenic plot were recaptured in border rows or trench traps outside the plot indicating a high level of dispersal activity. The long residency time and the high level of dispersal activity could increase the chances of development of a Bt-resistant beetle population. These findings are important to the development of a deployment strategy that will reduce the risk of build-up of Bt resistance in the beetle population.